The complete idiot's guide to a happy, healthy heart - Romaine, Deborah S. (Alpha Books, 1998)
You're no idiot, of course. You know smoking is bad for you and channel surfing doesn't constitute exercise. But when it comes to figuring out how to care for your heart, you feel like the Tin Man with a rusty ticker. Don't reach for the oil can just yet! The Complete Idiot's Guide to a Happy, Healthy Heart gives you the information you need on your bodys' most important muscle.